2009
DOI: 10.1016/j.jpedsurg.2008.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal outcomes associated with intestinal abnormalities diagnosed by fetal ultrasound

Abstract: Purpose Intestinal abnormalities are sometimes seen during antenatal testing, however the postnatal importance of these findings has not been well established. We evaluated whether abnormal intestinal appearance on fetal ultrasound (US) was ultimately related to neonatal outcome. Methods Fetal US exams from 2003–2006 were evaluated. Hyperechogenic bowel was defined as having the echogenicity comparable to bone, and dilated bowel was identified based on the sonographer’s assessment. Persistence or resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 10 publications
2
22
1
Order By: Relevance
“…Prenatal US findings suggestive of a JIA[8] (hypercogenic bowel, dilated fetal loops, polyhydramnios) were frequent in our series, but had no impact on the outcome. Patients with a PND had a lower median BW and GA. Possible misuse of Cesarean section in prenatally detected cases born in hospitals, without co-located surgical facilities, has been frequently reported, and the negative impact on the outcome of maturity and respiratory status has been hypothesized.…”
Section: Discussionmentioning
confidence: 70%
“…Prenatal US findings suggestive of a JIA[8] (hypercogenic bowel, dilated fetal loops, polyhydramnios) were frequent in our series, but had no impact on the outcome. Patients with a PND had a lower median BW and GA. Possible misuse of Cesarean section in prenatally detected cases born in hospitals, without co-located surgical facilities, has been frequently reported, and the negative impact on the outcome of maturity and respiratory status has been hypothesized.…”
Section: Discussionmentioning
confidence: 70%
“…While the prenatal diagnosis of duodenal atresia is highly accurate due to the pathognomonic ultrasound sign of the double-bubble, the literature has reported a sensitivity of prenatal ultrasound in the detection of small bowel atresia ranging from 23% up to 87% [8,9,10,11,12,13]. Jejunal atresia usually has higher sensitivity reaching 90% in some series [12].…”
Section: Discussionmentioning
confidence: 99%
“…Other prenatal US signs suggestive of CF are hiperechogenic bowel, echogenic masses or pseudocysts, ascites and intraperitoneal calcifications. Ruiz et al 2 evaluated neonatal outcome of abnormal intestinal appearance on fetal US and found that of 9 fetuses with persistent hyperechogenic bowel, 33.3% had meconium peritonitis or meconium ileus, and in 12 cases of prenatal dilated bowel, 66.7% born with an abnormality, most commonly intestinal atresia.…”
Section: Introductionmentioning
confidence: 99%